Methods of Corrective Treatment During the Rehabilitation Period after Allogeneic Transplantation for Acute Leukemia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigates pedagogical approaches that enhance the linguistic and academic development of bilingual learners in English as a Second Language (ESL) classrooms. Drawing on current research in applied linguistics, second language acquisition, and bilingual education, the study analyses instructional practices that support learners’ cognitive, sociocultural, and communicative needs. The research adopts a qualitative descriptive design grounded in classroom observation, teacher interviews, and analysis of instructional materials. Findings indicate that translanguaging, scaffolding, culturally responsive teaching, and task-based learning significantly contribute to bilingual learners’ engagement, metalinguistic awareness, and productive language use. The results further demonstrate that effective ESL instruction integrates learners’ first languages as cognitive resources rather than constraints, encourages collaborative meaning-making, and employs differentiated materials that reflect learners’ linguistic identities. The study contributes to ongoing discussions on inclusive ESL pedagogy and offers practical implications for teacher training and curriculum design.